The Effect of Chitosan-Silver Nanoparticles (Chi-AgNPs) Synthesized Using Clinacanthus nutans Extract on the Viability of MC3T3-E1 Preosteoblast Cells In Vitro - Sinta Candra Wardani; Muhammad Farand Sheva Rozano; Ariyati Retno Pratiwi; Che Azurahanim Che Abdullah; Rosnah Nawang (Odonto : Dental Journal, 2026)
Background: Chi-AgNPs (chitosan–silver nanoparticles) are antibacterial biomaterials with good biocompatibility potential, but their toxicity to osteoblastic cells still needs to be studied. This study aims to analyze the effect of Chi-AgNPs synthesized using Clinacanthus nutans extract on the viability of MC3T3-E1 preosteoblast cells at several concentrations to determine the safe concentration limit for their use.Method:  This laboratory experimental study used MC3T3-E1 cells exposed to Chi-AgNPs at concentrations of 12.5 µg/mL, 25 µg/mL, and 50 µg/mL, with a control group as a comparison. Cell viability was measured using the WST assay after 24 hours of incubation, then analyzed using the ANOVA test to see the differences between groups. Result: The results showed that a concentration of 12.5 µg/mL increased the average viability value by 30.8%, while a concentration of 25 µg/mL did not show a significant difference in cell viability compared to the control. Conversely, a concentration of 50 µg/mL caused a significant decrease in viability (p < 0.05), indicating toxicity related to the release of Ag⁺ ions and increased oxidative stress due to the small size of the nanoparticles (20 ± 3.93 nm). Conclusion: Chi-AgNPs are safe and biocompatible with MC3T3-E1 cells at concentrations below 25 µg/mL